1991
DOI: 10.1136/jnnp.54.6.524
|View full text |Cite
|
Sign up to set email alerts
|

Motor potentials of bulbocavernosus muscle after transcranial and lumbar magnetic stimulation: comparative study with bulbocavernosus reflex and pudendal evoked potentials.

Abstract: Motor potentials of the bulbocavernosus muscle were recorded in 17 healthy subjects after transcranial and lumbar magnetic stimulation. The latencies (SD) were respectively: (1-8) and 5 9 (04) ms. The central conduction time was 17-0 (2 5) ms. The bulbocavernosus reflex presented an onset at 34-5 (3 3) ms and a negative peak at 43-1 (3 9) ms. The cortical pudendal evoked potential was W shaped: the first peak had a latency of 35 4 (2 8) ms. The concurrent recording of motor potentials, bulbocavernosus reflex,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
14
1
1

Year Published

1997
1997
2003
2003

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 10 publications
4
14
1
1
Order By: Relevance
“…P1 latencies reported in the literature for the cortical PER range from 35 to 47 ms, and onset latencies for the BCR range from 20 to 40 ms. 1,7,8,16,19 Our results for these examinations fall within the reported ranges. The lack of a significant difference in the test latencies was expected, as the neural pathways for these responses are comparatively long and contain enough slack to mask slight changes in the latency of the evoked responses.…”
supporting
confidence: 86%
See 2 more Smart Citations
“…P1 latencies reported in the literature for the cortical PER range from 35 to 47 ms, and onset latencies for the BCR range from 20 to 40 ms. 1,7,8,16,19 Our results for these examinations fall within the reported ranges. The lack of a significant difference in the test latencies was expected, as the neural pathways for these responses are comparatively long and contain enough slack to mask slight changes in the latency of the evoked responses.…”
supporting
confidence: 86%
“…1,3,7,12,13,16,19 By performing these tests in healthy subjects with pharmacologic erections and utilizing penile monitoring to quantitate erectile function, we demonstrated that the calculated NCV increases with erection.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Several reports have been published on motor latencies of the external anal sphincter or pelvic floor muscles after magnetic stimulation of the lumbosacral roots. [4][5][6][7][8][9]13,15,16,18,21 Different recording electrodes have been used, but all have major disadvantages. The use of a needle electrode 4,15,16,18 or glovemounted electrode 6,8,9,21 is invasive and may be poorly tolerated by the patient.…”
mentioning
confidence: 99%
“…Most of them have targeted the external anal sphincter or the bulbocavernosus muscles [Opsomer et al, 1989[Opsomer et al, , 1990Dressler et al, 1990;Ertekin et al, 1990;Ghezzi et al, 1991Ghezzi et al, , 1992Herdmann et al, 1991;Brodak et al, 1993;Del Carro et al, 1993;Loening-Baucke et al, 1994;Jost et al, 1994;Jost and Schimrigk, 1994a,b;Pelliccioni et al, 1997;Hamdy et al, 1998;Jennum et al, 2001], whereas only a few have studied the external urethral sphincter [Snooks and Swash, 1984;Thiry and Deltenre, 1989;Eardley et al, 1990Eardley et al, , 1991. Separate branches of the pudendal nerve innervate the anal and urethral sphincters, and several studies have shown a functional dissociation between these branches in patients with lower urinary tract disease [Vereecken and Verduyn, 1970;Doyle et al, 1975;Sundin and Petersen, 1975;Blaivas et al, 1977Blaivas et al, , 1979Nordling and Meyho¡, 1979;Perkash, 1980;Snooks and Swash, 1985].…”
Section: Introductionmentioning
confidence: 99%